THE DEPENDENCE OF METALLOGENIC ZONES LOCATION FROM THE STRUCTURE OF THE BOTTOM OF THE CRUST SOUTH-EASTERN PART OF THE UKRAINIAN SHIELD - Pihulevskyi, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Brief performance Dneprovsk and Priazov metallogenic fields, Krivorozhsko-Kremenchug and Orekhovo-Pavlograd metallogenic zones is shown. The legitimacies of their intercoupling with plutonic constitution of the southeast part of Ukrainian Shield on depth 30 km are reviewed. The progressing granulite, gabbro-eclogite, peridotite, diorite, granite, diorite, granite, outlines mantle plum is shown, the conclusion about offset on depth of main faults of the southeast part of Ukrainian Shield is drawn.